2021
DOI: 10.1002/agm2.12190
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of directly‐acting antiviral therapy for chronic hepatitis C virus in elderly people

Abstract: Introduction In Italy, the prevalence of hepatitis C virus (HCV) infection is higher in the elderly, although the efficacy and safety of treatment in this population has not been extensively studied. Moreover, little is known about how much pharmacological interaction affects eligibility to treatment and to what extent the treatment affects subsequent outcomes. Methods We retrospectively analyzed the efficacy and safety of directly acting antivirals (DAAs), drug‐to‐drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…While this bias can be excluded only by a randomized trial design, we think that our cohort is reflective of the elderly HCV‐compensated population as 32% of the patients had more than two concomitant comorbidities, while 25% of our patients were taking at least five concomitant medications and lastly 24% had liver cirrhosis. These figures are similar to those reported by other Italian studies focusing on treatment with DAAs in elderlies, where SOF‐based regimens were the most commonly used DAAs 13,17,18 . We are also aware of the limitations stemming from the inclusion of patients managed in expert tertiary referral centres; however, this was not the consequence of a flawed study design but rather than treatment in Italy is still restricted to specialist care.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…While this bias can be excluded only by a randomized trial design, we think that our cohort is reflective of the elderly HCV‐compensated population as 32% of the patients had more than two concomitant comorbidities, while 25% of our patients were taking at least five concomitant medications and lastly 24% had liver cirrhosis. These figures are similar to those reported by other Italian studies focusing on treatment with DAAs in elderlies, where SOF‐based regimens were the most commonly used DAAs 13,17,18 . We are also aware of the limitations stemming from the inclusion of patients managed in expert tertiary referral centres; however, this was not the consequence of a flawed study design but rather than treatment in Italy is still restricted to specialist care.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, De Santis and colleagues, 17 who evaluated the efficacy and safety of multiple DAA regimens in patients older than 70 years found that in this cohort of 138 patients, of whom 34 (24.6%) received G/P for 8 or 12 weeks, SVR12 was achieved in 98% of patients. Interestingly, the authors found a higher incidence of itching in patients treated with G/P than those treated with other regimens (17% vs 3%), with G/P confirmed to be a risk factor for itching (odds ratio 3.6, p = 0.03) by logistic regression analysis 17 …”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations